An exploratory study on participative content creation in the Dream SMP (Survival Multiplayer) fandom - Madrangca, Heaven Aj F. (College of Communication, Art, and Design , University of the Philippines Cebu, 2023)
The Dream SMP (Survival Multiplayer) is an invite-only, survival multiplayer Minecraft server known for its live roleplay and narrative building through live streams on YouTube and Twitch, a storytelling medium that is new and unprecedented. This study examines the fan-made content produced by the DSMP fan community, how the fandom interprets and makes sense of its story, and its impacts on the canonical narrative. The research used Focused Group Discussion (FGD), Interviews, and descriptive analysis through the theoretical lenses of Peircean Semiotics, Reader- Response Criticism, and Symbolic Interactionism to achieve its objectives. This thesis found that fanmade content was used to naturalize and concretize the DSMP storyline, and even had significant effects on its storyline. The research also revealed that DSMP fans enjoyed the participative nature of the medium, contributing to their immersion and investment in the storyline. Fanmade content revealed what the DSMP community deemed as crucial plot elements (through fan documentation), and more importantly, aided in naturalizing and humanizing the canon content by creating more ?natural? visuals (through fan artworks and fan animation) or exploring character introspection and their relationships (through fanfiction and fan songs). Finally, due to the intertwined nature of the Content Creators and fans, the DSMP canon storyline integrated many fanmade content into their canon storyline, which included character designs, character traits and personalities, and even new characters.